Politik Hukum Poligami (Studi terhadap Peraturan Perundang-Undangan di Negara-Negara Muslim) - Marzuki, Ismail (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
This article discusses Islamic family law politics about regulating polygamy in Muslim countries. The policy of Islamic law in Muslim countries in the modern era can be categorized into two, namely uncodified law, and codified law. The Muslim countries discussed in this article are Muslim countries whose legal politics fall into the codified law category, namely: Turkey, Tunisia, Iran, Indonesia, Egypt, Morocco, and Afghanistan. Although according to fiqh polygamy is something permissible, in practice each Islamic country has a different legal policy related to polygamy, namely: (1) some countries allow polygamy, (2) some allow polygamy with strict conditions, and (3) some prohibit polygamy. In addition, this article also discusses the "progress" of legal policies regarding polygamy from the jurisprudence school of law that are commonly adhered to in each of these Islamic countries. This article shows that legal policies regarding polygamy in Islamic countries included in the codified law category have a variety of styles, some are liberal, conservative, and some are moderate.